2021
DOI: 10.5935/0103-507x.20210059
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation versus conventional oxygen therapy after extubation failure in high-risk patients in an intensive care unit: a pragmatic clinical trial

Abstract: Objetivo Determinar la efectividad de la ventilación no invasiva frente a oxigenoterapia convencional en pacientes con insuficiencia respiratoria aguda tras fracaso de la extubación. Métodos Ensayo clínico pragmático realizado una unidad de cuidados intensivos de marzo de 2009 a septiembre de 2016. Se incluyeron pacientes sometidos a ventilación mecánica > 24 horas, y que desarrollaron insuficiencia respiratoria aguda tras extubación programada, siendo asignados a venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…( 16 ) Finally, NIV to treat postextubation respiratory failure in non-COVID-19 patients also reduced the need for reintubation in a recent randomized clinical trial. ( 11 ) There are limited data on these three modes of NIV use during weaning in COVID-19 patients. In an observational study, Cammarota et al found that the strategy of early extubation followed by immediate NIV was chosen in 54.5% of patients and reduced both the duration of invasive MV and the need for reintubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 16 ) Finally, NIV to treat postextubation respiratory failure in non-COVID-19 patients also reduced the need for reintubation in a recent randomized clinical trial. ( 11 ) There are limited data on these three modes of NIV use during weaning in COVID-19 patients. In an observational study, Cammarota et al found that the strategy of early extubation followed by immediate NIV was chosen in 54.5% of patients and reduced both the duration of invasive MV and the need for reintubation.…”
Section: Discussionmentioning
confidence: 99%
“…Early extubation followed by immediate NIV, prophylactic NIV after extubating a patient who tolerated a spontaneous breathing trial (SBT), and NIV as rescue therapy for postextubation respiratory failure are applied during weaning from MV. ( 9 - 11 ) To date, there have been very few investigations on the role of NIV in weaning COVID-19 patients from MV.…”
Section: Introductionmentioning
confidence: 99%
“…NIV may be used in patients with mild-moderate respiratory acidosis [5], as it can improve dyspnoea and gas exchange, and may reduce the incidence of tracheal intubation [6]. The diagnostic groups typically requiring NIV include those with chronic obstructive pulmonary disease (COPD), obesity and neuromuscular disease [7,8 ▪ ,9]. Early application of NIV for patients with acute on chronic hypercapnic respiratory failure refractory to optimised medical therapy improves a range of outcomes, including resolution of hypercapnia, reduced risk of requiring IMV and reduced hospital mortality [10].…”
Section: Use Of Noninvasive Ventilation In Critical Carementioning
confidence: 99%